Serangan Israel Terhadap Lebanon dikaitkan dengan Prinsip-Prinsip Hukum Humaniter - Suwandi, Sri Setianingsih (Indonesian Journal of International Law, 2021)
Israel’s attacked to Hezbollah at Lebanon has arisen international reactions because of enormoue victims caused by that action, whom mostly were civilians. International society has asked the United Nations Security Council to pass a Resolution for handling this problem based on the authority stipulated in the United Nations by United Syastes as one of the Security Council’s member, finally the Resolution contains essential element which stated that the situation in Lebanon has caused breach to international peace and safety. Security Council Resolution Number 1701 is a good starting point to change the regional reality become one goal, to keep the peace and safety in Lebanon, which has been desired by international community. Final result of this Resolution however depends on intention of the parties to comply with it because it has no sanction mechanism. Based on Article 25 of the United Nations Charter, Security Coincil’s decision legally binds all member of the United Nations, and those countries, which are not member, shoul act according to this Resolution for the peace and safety of international world.